Reflections of an adolescent perpetrator of violence: Men and feminism - Reyes Ibarra, Vanessa Lilian (2022)
Using a case study, this paper focuses on the possibilities for a male adolescent to reflect, question and make ruptures on his own exercises of violence and on the interpellations he has experienced with women and feminism. Despite the negative consequences it entails, the repetition of rigid male gender roles and male mandates associated with violence, is often maintained as part of a male identity marked by dominance. However, gender socialization, as a process in continuous construction, opens the possibility for male adolescents to question the rigid learning acquired in childhood. It is concluded that adolescents who exercise violence can question themselves and break with previously acquired mandates associated with violence.